Complication rates in rigid vs. flexible endoscopic foreign body removal in children. (March 2023) - Wiemers, Anna; Vossen, Christina; Lücke, Thomas; Freitag, Nadine; Nguyen, Thi Minh Thao Lea; Möllenberg, Leon; Pohunek, Petr; Schramm, Dirk
Abstract: While foreign body aspiration remains a frequent and preventable cause of morbidity and mortality in children, recommendations on the appropriate removal technique do often not match the lived practice and expertise of the performing examiners. As there is a scarcity of data regarding success and complication rates of the procedure, the aim of this study was to set up a classification system for procedure-related complications, prospectively record and analyze them. Specialists in the field of foreign body removal contributed cases anonymously. Information regarding procedural details of the bronchoscopy, type, and severity of complications as well as patient characteristics were classified and recorded. Correlations were calculated using Pearson's Chi Square test. A total of 314 rigid and 178 flexible bronchoscopies were compared. Complications were categorized and their severity was defined by the anesthesiologist's assessment of whether to interrupt or terminate the procedure. The overall complication rate was similar in rigid vs. flexible bronchoscopy (19.1% vs. 24.2%, p = 0.232), while respiratory complications occurred significantly less frequent during rigid bronchoscopy (9.2% vs. 16.3%, p = 0.025). This is the largest pediatric case collection recording and comparing complications between rigid and flexible foreign body removal. The higher rate of respiratory complications in flexible bronchoscopy has been shown for the first time and validates some of the concerns about its use for foreign body removal. Flexible bronchoscopy is a safe procedure when extended respiratory monitoring and the possibility of an immediate switch to a secured airway are assured.